اجتہاد کامفہوم ،ثبوت، اہمیت اور تقاضے، ایک ارتقائی مطالعہ: The Meaning of Ijtihad, Evidence, Importance and Requirements, an Evolutionary Study - Ghulam Dastgir Ahmad,; Dr. Abbas Ali Raza, (Al Manhal Research Journal, 2024)
Ijtihad, a term derived from the Arabic root "j-h-d," meaning "to strive" or "to exert effort," is a fundamental concept in Islamic jurisprudence. It refers to the process of independent legal reasoning and interpretation by qualified scholars to derive legal rulings from the primary sources of Islamic law, namely the Quran and the Sunnah (the teachings and practices of the Prophet Muhammad). This paper aims to provide a comprehensive understanding of ijtihad, its evidence, importance, and requirements, through an evolutionary study that traces its development from the early period of Islam to the present day. The study begins by examining the historical context in which ijtihad emerged, highlighting its significance in addressing new legal issues and adapting Islamic law to changing social and cultural contexts. It then explores the various sources of evidence used in ijtihad, including the Quran, the Sunnah, consensus (ijma), and analogical reasoning (qiyas), as well as the principles of legal interpretation (usul al-fiqh) that guide the process. Finally, the study examines the requirements for engaging in ijtihad, including the acquisition of specialized knowledge in Islamic law, proficiency in Arabic, and adherence to ethical standards. It also discusses the challenges and controversies surrounding ijtihad, such as the tension between tradition and innovation, the role of personal discretion, and the potential for abuse or misuse. Overall, this paper provides a comprehensive overview of ijtihad, shedding light on its meaning, evidence, importance, and requirements, and highlighting its ongoing relevance and significance in contemporary Islamic thought and practice.